A experiência grupal em trajetos autoformativos: imaginário social e narrativas - Pereira, Carmem Silvia Rodrigues (2020)
This master's thesis was developed in Research Line 1 - Training, Knowledge and Professional Development, of the Postgraduate Program in Education, Master in Education, at the Education Center, at the Federal University of Santa Maria (UFSM). The dissertation proposed an investigation that aimed to identify the instituted and instituting processes provoked in the members of the Study and Research Group in Education and Social Imaginary - GEPEIS during their self-forming trajectory in this group, through the social imagery and interrelated narratives with your praxis. The investigation was dedicated to knowing what were the meanings of the social imaginary that permeate the self-formation of the investigated co-authors and to understand what the self-forming processes triggered by GEPEIS, in the co-authors. Theoretical discussions were based on the Social Imaginary, by Cornelius Castoriadis, to discuss the training and self-training of GEPEIS members, always considering the contributions of training, self-training, group and group learning. GEPEIS has been working with research, teaching and extension over the last 27 years, in the area of Teacher Education, based on the theoretical field of Social Imaginary, by Cornelius Castoriadis (1982).Thus, one can think of the act of creating and constituting imaginary social meanings, not in the unreal or metaphorical sense, but in the inventive and creative capacity that is inherent to human beings. Creative processes and meanings, something that introduces the new, constitutes the unprecedented, the temporality, the position of new systems of meanings and signifiers. The methodological devices consisted of self-forming processes (JOSSO, 2010), involving the field of autobiography with a focus on co-authors and their experiences, constituting reflections around the imagery of the members researched here, between the years 1993 to 2020. The results obtained say of importance of the group as a device in its formation, contributing to the personal and professional formation of its members and the imaginary that institutes education. The educational process can become significant for the human being when he is looking for what he adds in his training, which can make him sucessful (TARDIF, 2002). There is no point professionalizing yourself in pratice, understanding the need for continuous qualification, adopting a reflexive practice, without developing the ability to change, which often implies unlearning to relearn. Through narratives we have access to the personal dispositions of the human being and their meanings in the face of his personal and professional life. Art brings us to the narrative through the intrinsic relationship between the two: the narrative can be a plot of art and art can be a narrative. Life narratives have become a methodology within the scope of group research, being a training and investigation device, intertwining in the face of their peculiarities and meanings